Treatment of pain in chronic pancreatitis by inhibition of pancreatic secretion with octreotide. Issue 3 (March 1995) - Malfertheiner, P; Mayer, D; Büchler, M; Domínguez-Muñoz, J E; Schiefer, B; Ditschuneit, H
Abstract : It has been suggested that pancreatic ductal hypertension, secondary to pancreatic outflow obstruction, is a cause of pain in chronic pancreatitis. This study investigated the effect of inhibiting pancreatic secretion with octreotide in chronic pancreatitis pain. Ten patients with chronic alcoholic pancreatitis and severe daily pain were included in an intraindividual double blind crossover study. All patients received octreotide (3 x 100 micrograms/day subcutaneously) and placebo (3 x 0.9% saline solution subcutaneously) for three days at random. Between both treatment phases a two day washout period was interposed. Intensity of pain (visual analogue scale) and analgesic consumption were carefully registered. Pancreatic secretion was monitored daily by measuring faecal chymotrypsin concentration. It was found that during the administration of octreotide, pancreatic secretion was strongly inhibited (faecal chymotrypsin mean (SD) 1.7 (0.6) U/g) with respect to placebo (9.6 (4.2) U/g) and washout (7.6 (3.1) U/g) periods (p < 0.001). Pain score (29.6 (4.5) v 28.7 (5.8)) and consumption of analgesics were no different during the octreotide and placebo periods. It is concluded that short term inhibition of pancreatic secretion does not result in pain relief in patients with chronic pancreatitis. This finding is in contrast with the hypothesis that outflow obstruction of pancreatic secretion with consequent ductal hypertension is an important cause of severe persistent pain in chronic pancreatitis.